KEPASTIAN HUKUM PENENTUAN BATAS MINIMAL USIA DEWASA DALAM PENDIRIAN PERSEROAN PERSEKUTUAN MODAL DI INDONESIA - Aulia, Faturrahman; Sunarmi, Sunarmi; Sukaraja, Detania (Smart Education, 2025)
Abstract: This study discusses legal certainty in determiningthe minimum age limit foradults in establishing a capitalpartnership in Indonesia. The ambiguityoftheregulationoftheageofadulthood in Law Number 40 of 2007 concerningLimitedLiabilityCompaniesanditsrevisionthrough Law Number 6 of 2023 concerningJobCreation has givenrisetodiverseinterpretationsamongnotariesand legal practitioners. This study uses a normative legal approachsupportedbyempirical data frominterviewswithnotaries in Medan and Binjai. The resultsofthe study showthattheabsenceof a clear minimum age limit givesrisetomultipleinterpretationsand has animpacton legal uncertainty in establishing a company. Therefore, harmonizationofregulationsandtheestablishmentofexplicitrules are neededtoensure legal certainty. Keyword:Legal Certainty, Age of Adulthood, Company, Capital Partnership Abstrak:Penelitianinimembahaskepastianhukumdalampenentuan batas minimal usiadewasadalampendirianperseroanpersekutuan modal di Indonesia. KetidakjelasanpengaturanusiadewasadalamUndang-UndangNomor 40 Tahun 2007 tentang Perseroan TerbatassertarevisinyamelaluiUndang-UndangNomor 6 Tahun 2023 tentang Cipta Kerjatelahmenimbulkankeragamanpenafsiran di kalangannotaris dan praktisihukum. Penelitianinimenggunakanpendekatanyuridisnormatifdengandukungan data empirisdariwawancaraterhadapnotaris di Medan dan Binjai. Hasil penelitianmenunjukkanbahwatidakadanya batas usia minimal yang tegasmenimbulkanmultitafsir dan berdampak pada ketidakpastianhukumdalampendirianperseroan. Oleh karenaitu, dibutuhkanharmonisasiregulasisertapenetapanaturan yang eksplisituntukmenjaminkepastianhukum. Kata kunci: Kepastian Hukum, Usia Dewasa, Perseroan, Persekutuan Modal